2022
DOI: 10.1039/d2ta01064j
|View full text |Cite
|
Sign up to set email alerts
|

Regulating solvation and interface chemistry to inhibit corrosion of the aluminum anode in aluminum–air batteries

Abstract: As a promising energy storage technology, aluminum-air batteries possess the advantages of high energy density, safe and low-cost. However, the severe self-corrosion of aluminum anode greatly limits their practical applications....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…This “water-in-salt” structure not only gives the electrolyte excellent performance with a specific capacity of 2324 mA h g −1 and an inhibition efficiency of 82.78% but also enables the generation of Al(OH) 3 . As an extension of the high-concentration salt electrolyte, Lv et al 88 combined a high-concentration salt (8 M KOAc) with the traditional inorganic additive sodium stannate. As illustrated the electrolyte can introduce a protective layer at the interface, which can adjust water activity and improve corrosion inhibition efficiency.…”
Section: Aqueous Electrolytes For Aabsmentioning
confidence: 99%
“…This “water-in-salt” structure not only gives the electrolyte excellent performance with a specific capacity of 2324 mA h g −1 and an inhibition efficiency of 82.78% but also enables the generation of Al(OH) 3 . As an extension of the high-concentration salt electrolyte, Lv et al 88 combined a high-concentration salt (8 M KOAc) with the traditional inorganic additive sodium stannate. As illustrated the electrolyte can introduce a protective layer at the interface, which can adjust water activity and improve corrosion inhibition efficiency.…”
Section: Aqueous Electrolytes For Aabsmentioning
confidence: 99%
“…[316] Novel electrolyte system, such as high-strength agarose gel electrolyte, was studied. [317] Several works proposed various corrosion inhibitors that could enhance the Al anode corrosion resistance without affecting the battery performance, which include sodium stannate, [318] cerium chloride, [319] aromatic acids (benzoic acid, iso-phthalic acid, trimesic acid, amiono acids), [320] quaternary ammonium-type surfactants, [321] ellagic acid and Na 2 SnO 3 , [322] chrysanthemum coronarium leaves extract, [323] potassium sodium tartrate tetrahydrate and sodium stannate trihydrate, [324] and alkyl polyglucoside and K 2 SnO 3 . [325] Harchegani and Riahi showed that the pure Al anode selfcorrosion resistance was significantly improved by adding 1.0 wt % CeCl 2 .…”
Section: Al-airmentioning
confidence: 99%
“…29 Moreover, the low solubility of Al(OH) 3 triggers microcrystal agglomeration, thus giving rise to numerous precipitates in pHneutral AABs. The precipitates cause a sharp increase in electrolyte viscosity and cell polarization, 30 which in turn diminish battery's endurance much below theoretical expectations. As a result, for pH-neutral AABs, it is highly desired to develop effective strategies to regulate the interfacial reaction and achieve uniform Al stripping behavior for realizing highperformance AABs.…”
Section: Introductionmentioning
confidence: 96%